Measuring Women's Empowerment in Sub-Saharan Africa: Exploratory and Confirmatory Factor Analyses of the Demographic and Health Surveys - Asaolu, Ibitola O.; Alaofè, Halimatou; Gunn, Jayleen K. L.; Adu, Akosua K.; Monroy, Amanda J.; Ehiri, John E.; Hayden, Mary H.; Ernst, Kacey C. (Frontiers in Psychology, 2018)
Background: Women’s status and empowerment influence health, nutrition, and socioeconomic status of women and their children. Despite its benefits, however, research on women’s empowerment in Sub-Saharan Africa (SSA) is limited in scope and geography. Empowerment is variably defined and data for comparison across regions is often limited. The objective of the current study was to identify domains of empowerment from a widely available data source, Demographic and Health Surveys, across multiple regions in sub-Saharan Africa. Methods: Demographic and Health Surveys from nineteen countries representing four African regions were used for the analysis. A total of 26 indicators across different dimensions (economic, socio-cultural, education, and health) were used to characterize women’s empowerment. Pooled data from all countries were randomly divided into two datasets—one for exploratory factor analysis (EFA) and the other for Confirmatory Factor Analysis (CFA)—to verify the factor structure hypothesized during EFA. Results: Four factors including attitudes towards violence, labor force participation, education, and access to healthcare were found to define women’s empowerment in Central, Southern, and West Africa. However, in East Africa, only three factors were relevant: attitudes towards violence, access to healthcare ranking, and labor force participation. There was limited evidence to support household decision-making, life course, or legal status domains as components of women’s empowerment. Conclusion: This foremost study advances scholarship on women’s empowerment by providing a validated measure of women’s empowerment for researchers and other stakeholders in health and development.